2022
DOI: 10.1039/d2cp02330j
|View full text |Cite
|
Sign up to set email alerts
|

MXene-modified molecularly imprinted polymers as an artificial bio-recognition platform for efficient electrochemical sensing: progress and perspectives

Abstract: The development of efficient electrochemical sensors of exceptional features, molecularly imprinted polymers (MIPs) have been extensively utilized due to their great vitality as an alternative to bio-recognition elements. MIPs as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 93 publications
0
14
0
1
Order By: Relevance
“…In the last decade, the science of biosensing has seen tremendous progress in illness diagnostics 90,91 . Drug‐resistant bacteria are surpassing drug discovery efforts, putting current antibiotics in jeopardy and threatening numerous unavoidable medical procedures which are taken for granted 92–94 . Controlling this worldwide threat will require the invention and application of increasingly wide‐ranging diagnostics for infectious diseases.…”
Section: Recent Advances In Microbial Sensingmentioning
confidence: 99%
“…In the last decade, the science of biosensing has seen tremendous progress in illness diagnostics 90,91 . Drug‐resistant bacteria are surpassing drug discovery efforts, putting current antibiotics in jeopardy and threatening numerous unavoidable medical procedures which are taken for granted 92–94 . Controlling this worldwide threat will require the invention and application of increasingly wide‐ranging diagnostics for infectious diseases.…”
Section: Recent Advances In Microbial Sensingmentioning
confidence: 99%
“…✓ In composite formation, MXene is hybridized with various molecules via non-covalent or physical interactions mostly. [436] These interactions are weaker and not stable for biomolecule sensing.…”
Section: Current Challenges Future Prospects and Conclusion For Mxene...mentioning
confidence: 99%
“…But they have been considered rarely while considering MXene‐based biosensing. ✓In composite formation, MXene is hybridized with various molecules via non‐covalent or physical interactions mostly. [ 436 ] These interactions are weaker and not stable for biomolecule sensing. ✓Similarly, during the composite form of the MXenes, ultra‐sonication is applied which leads to the breakage of the MXene flakes and decreased size. The properties of the MXenes are completely dependent on flake size and it is ignored to a larger extent in the literature.…”
Section: Current Challenges Future Prospects and Conclusion For Mxene...mentioning
confidence: 99%
“…MXene has shown excellent catalytic, electronic and magnetic properties, and has a range of practical applications, such as electrocatalysis, [15][16][17] lithium-ion batteries, [18][19][20] electromagnetic shielding 21 and electronic devices. 22,23 In particular, for electrocatalytic hydrogen evolution, the high specific surface area, excellent electronic conductivity and adjustable surface termination of MXene materials make them a promising candidate for low-cost HER catalysts. [24][25][26] However, it is reported that the key catalytic performances of pure MXenes are still far from ideal, in the aspects of both H adsorption energy and the reaction rate.…”
Section: Introductionmentioning
confidence: 99%